Study of Social Competence Level among Secondary Schools’ Students in Khyber Pakhtunkhwa - Ahmad, Naseer; Irshadullah, Hafiz Muhammad (Annals of Human and Social Sciences, 2024)
The aim of this study was to assess the social competence level of secondary school students. This was a single-method design quantitative study. Cross-sectional survey type technique was used. The population of study was all the secondary school students in Khyber Pakhtunkhwa. A sample of 560 secondary students, 27 from each of 28 secondary schools were randomly selected. For data collection, a questionnaire.i.e.4-point Likert type scale developed by Shujja et al. (2015) was used for assessment of students’ social competence level. The validity of scale was checked with the help of expert committee while reliability was checked through Cronbach Alpha and was determined as 0.726. Data were analyzed with the help of SPSS, on the basis of research question using frequency distribution, independent sample t-test and ANOVA. From the findings, it is concluded that social competence level is different for different students. So the development of students’ social competence is recommended and for this, intervention/training is suggested at school level.